1996
DOI: 10.1080/01635589609514452
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids, vitamin A, and estrogen receptor status in breast cancer

Abstract: Among patients with breast cancer, tumors that contain estrogen receptors (ER) are associated with improved survival and better response to hormone therapy than those not expressing these receptors. The purpose of these case comparison studies was to examine the relationship between carotenoids, vitamin A, and the tumor ER status in women at diagnosis of primary breast cancer. The focus of the first study was the relationship between dietary intake and ER status, and the focus of the second study was the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…However, the magnitude of the inverse association with fruit intake was stronger in our study than in prospective studies [4], which may be due to recall bias in case-control studies. Our results for fruit intake were stronger for ER+ than ER-tumors and are consistent with the other published case-control studies [9][10][11]. The largest prospective study to date, in contrast, found that vegetable intake was inversely associated with ER-breast tumors [13].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the magnitude of the inverse association with fruit intake was stronger in our study than in prospective studies [4], which may be due to recall bias in case-control studies. Our results for fruit intake were stronger for ER+ than ER-tumors and are consistent with the other published case-control studies [9][10][11]. The largest prospective study to date, in contrast, found that vegetable intake was inversely associated with ER-breast tumors [13].…”
Section: Discussionsupporting
confidence: 93%
“…However, results for fruit and vegetable intake have been inconsistent. The three casecontrol studies [9][10][11] have all found the inverse association between fruit and vegetable intake to be stronger for ER+ than ER-breast tumors. The two prospective studies that have evaluated this question [12,13] have provided contradictory results.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have produced inconsistent results with regard to the intake of fruit, vegetable, and micronutrients based on ER status (27)(28)(29)(30)(31)(32)(33)(34). In a cohort study of postmenopausal women, dietary intake of selected antioxidants was inversely associated with breast cancer characterized by both ER and PR, but not with those jointly defined by ER and PR status (21).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that dietary components can influence ER status [69,70,71,72]. The ER-α is necessary for the proliferative effects of estradiol in breast cancer cells and is overexpressed in the transformed state [73,74,75,76].…”
Section: Estrogen and Breast Cancermentioning
confidence: 99%